2015
DOI: 10.3923/ijss.2015.186.194
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Soil Amendments on Growth, Seed Yield and NPK Content of Bottle Gourd (Lagenaria siceraria) Grown in Clayey Soil

Abstract: The application of bio-fertilizers and organic fertilizer is considered a promising alternative for mineral fertilizers to decrease the production costs and environmental pollution with good yield. Hence, the present study aimed to evaluate the benefits of rice straw compost, humic acid and effective microorganism alone or in combination as an alternative to mineral-N fertilizer on the growth, foliar NPK content and yield of the local variety of bottle gourd. The study was carried out at Barramoon experimental… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
4
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 16 publications
3
4
1
Order By: Relevance
“…Through literature search there is limited result on this finding, although potassium is required to promote vegetative growth and development by playing a major role in many physiological processes such as cell division and elongation [11], this study indicated that Arctium lappa requires relatively low potassium for optimum growth performance. This result is in contrast to the early study where the elevated application of potassium significantly(p<0.05) increased the yield of these growth parameters in different cultivated species [12,13].…”
Section: E Statistical Analysiscontrasting
confidence: 99%
“…Through literature search there is limited result on this finding, although potassium is required to promote vegetative growth and development by playing a major role in many physiological processes such as cell division and elongation [11], this study indicated that Arctium lappa requires relatively low potassium for optimum growth performance. This result is in contrast to the early study where the elevated application of potassium significantly(p<0.05) increased the yield of these growth parameters in different cultivated species [12,13].…”
Section: E Statistical Analysiscontrasting
confidence: 99%
“…The K contents in both trials were statistically identical with all the treatments except T 8 and T 15 treatments, where field temperature and saturated moisture condition of soil were practiced without the application of any organic amendments (Table 4). The observations of the present study have been coincided with those reported by prior investigators [18,24,25]. Only 2.61% of the total variation in K availability of soil in first trial and 35.11% of variation in second trial could be demonstrated by C/N ratios in both seasons ( Fig.…”
Section: Bioavailability Of Potassiumsupporting
confidence: 93%
“…Soil OC content was increased with soil temperature rise. Almost similar aptitudes have also been reported by previous researchers [18,19,20]. Temperature rise may support high plant productivity and organic matter input to soil and consequently increases soil OC content [9].…”
Section: Changes In Soil Organic Carbonsupporting
confidence: 85%
“…Further, the application of higher nutrient rates particularly nitrogen in F 1 might have produced residual acidity associated with N-fertilizers during the nitrification process. Similar results were also reported by Chaudhary et al [14] and Ibrahim et al [15]. The OC content of the soil in the present investigation ranged from 5.1 to 5.8 g kg -1 (Table 1).…”
Section: Soil Propertiessupporting
confidence: 92%